Rapid identification of Bactrocera zonata (Dip.: Tephritidae) using TaqMan real-time PCR assay - Koohkanzade, Marzieh (PLoS One, 2018)
Tephritid fruit flies are ranked as one of the most damaging groups of insect pests. Morphological identification of fruit flies is mainly performed on adults due to the lack of adequate identification keys for immature stages. The peach fruit fly, Bactrocera zonata (Saunders), infests some of the principal commercial fruits and vegetables. It is, therefore important to avert its global dispersal, particularly by accurately identifying this species at ports of entry. In this study, a TaqMan real-time polymerase chain reaction (PCR) was developed for the accurate identification and sensitive detection of the peach fruit fly. A novel set of primers and probe were designed to specifically identify the mitochondrial cytochrome oxidase I (COI) gene. All specimens of peach fruit fly (including various life stages) were detected, and no cross reactivity with other tested tephritids were observed. Since this assay performed equally well with crushed insects and purified DNA, we note added efficiency by eliminating DNA extraction step. Considering the speed, specificity as well as sensitivity of the assay, Taqman real-time PCR can be used as a swift and specific method for pest species at ports of entry.